KEPRIBADIAN TOKOH UTAMA DALAM NOVEL TELEMBUK DANGDUT DAN KISAH CINTA YANG KEPARAT - Astuti, Andriani Widi; Kasnadi, Kasnadi; Setiawan, Heru (Jurnal Bahasa dan Sastra, 2022)
Personality psychology is a study that discusses personality in literary works. In the novel Telembuk Dangdut dan Kisah Cinta yang Keparat by Kedung Darma Romansa, which tells the story of a young woman who sells her pride to fulfill her life needs. This study aims to describe the id, ego and superego of the main character in the novel above. This study uses a qualitative research design. The data was collected using the technique of observing and recording findings related to the psychological data of the main character’s personality in the novel. The data were analyzed based on Freud’s theory of personality psychology which consisted of: id, ego and superego. The id of the main character (Safitri) who works as a prostitute to fulfill her life needs. On the other hand, she often gives and helps others. Safitri’s ego will stop working as a prostitute if she marries her expected man. The superego of Safitri’s character is undecided in making life choice with her mother or lovershe loves.